Reverse dorsal metacarpal artery flap: a review - Ordaz, Erick Hidrogo; Ayala, Ezequiel Salcedo Ignacio; Sánchez, Luis Fernando Bustamante; Kutugata, Luis Carlos Dávila; Inzunza, José Enrique Santiesteban; Nájera, Iberia Maria Ossa; Sánchez, Pablo Alberto Mendoza; Jiménez, Hector Ulises Quiroga; Vázquez, Rogelio Romero (International Journal of Research in Medical Sciences, 2024)
Deep soft tissue injuries around the thumb can significantly impair hand function if not managed appropriately. Various surgical options exist for treating these complex lesions, including microsurgical flaps, local flaps, and distant pedicled flaps. The dorsal metacarpal artery (DMCA) family of flaps belongs to the latter category. These versatile flaps can be designed as racquet-shaped, island, or bilobed flaps, utilizing the first DMCA alone or in combination with the second DMCA. In this review, we explore the surgical anatomy, techniques, and clinical applications of reversal DMCA flap (RDMA).